FLATTENING ORGANIZATIONAL STRUCTURES THROUGH AI INTEGRATION: IMPACTS ON MANAGERIAL EFFECTIVENESS - Anita Kusuma Dewi; Fitri Melawati; Betti Widianingsih (INJOSEDU: International Journal of Social and Education, 2026)
The development of artificial intelligence (AI) has driven significant changes in modern organizational structures, particularly in efforts to create more flexible, adaptive, and efficient organizations. This study aims to analyze the influence of AI integration on the process of streamlining organizational structures and its impact on managerial effectiveness. The research method used is a literature review by examining various scientific articles, international journals, industry reports, and academic publications relevant to digital transformation, AI in management, and the dynamics of organizational structures. The analysis was conducted descriptively and conceptually to identify the relationship between AI implementation, the reduction of organizational hierarchies, and changes in managerial roles in decision-making. The results of the study indicate that AI integration can reduce organizational dependence on complex bureaucratic structures through process automation, accelerated information flow, and increased transparency in internal communications. These conditions enable organizations to build flatter structures with shorter and more responsive coordination paths. Furthermore, managerial effectiveness is increased through the support of data-driven systems that facilitate real-time planning, monitoring, and performance evaluation. However, this transformation also presents challenges in the form of changes in organizational culture, the need to improve digital competencies, and potential resistance from middle management. This study concludes that AI integration plays a crucial role in driving organizational efficiency and redefining managerial functions toward more collaborative, strategic, and technology-driven leadership styles.